A case report of lymphangioleiomyomatosis with retroperitoneal masses in pregnancy - Zhu, Yashi; Wang, Chao; Ding, Jianyi; Yang, Meiqin; Bo, Yin; Ma, Mingjun; Hu, Haoran; Cheng, Jiejun; Han, Lingfei; Wang, Yu (Frontiers in Medicine, 2023)
Background: Lymphangioleiomyomatosis is a rare, slowly progressive tumor of unknown etiology, almost only occurring in women of childbearing age.Characterized by abnormal proliferation of pulmonary smooth muscle cells, extrapulmonary lymphangioleiomyomatosis without pulmonary invasion is rarely reported. Due to its rarity, we want to report a case of primary retroperitoneal lymphangioleiomyomatosis during pregnancy, which is easy to be misdiagnosed.A 31-year-old woman with unintended pregnancy was in the 13 th week of pregnancy when a routine obstetrical ultrasound showed a cystic-solid mass with rich blood signals in the pelvic cavity. The patient had no clinical symptoms and then underwent a complete curettage. 24 days after the operation, the patient was readmitted again for further diagnosis. The imaging examination showed the mass had enlarged, wrapped around the abdominal aorta and inferior vena cava, and compressed the middle and lower segment of the ureter. After a multi-disciplinary discussion and patient explanation, we performed an exploratory laparotomy for the patient, and the tumor was completely removed. The intraoperative pathological examination and immunohistochemical staining showed the retroperitoneal mass with no evidence of malignancy. The overall morphologic and immunophenotypic features supported the diagnosis of lymphangioleiomyomatosis. The postoperative evolution was uneventful and the patient was discharged.: Pregnancy with retroperitoneal lymphangioleiomyomatosis should be kept in mind in the differential diagnosis of pelvic and abdominal masses. It is hard to diagnose preoperatively by ultrasound or CT scan. The best treatment is radical surgery, surgeons should consider the fetal and maternal conditions comprehensively when formulating a treatment plan.